Lexico-semantic effects on word naming in Persian: Does age of acquisition have an effect? - Bakhtiar, Mehdi; Weekes, Brendan (Memory & Cognition, 2015)
The age of acquisition (AoA) of a word has an effect on skilled reading performance. According to the arbitrary-mapping (AM) hypothesis, AoA effects on word naming are a consequence of arbitrary mappings between input and output in the lexical network. The AM hypothesis predicts that effects of AoA will be observed when words have unpredictable orthography-to-phonology (OP) mappings. The Persian writing system is characterized by a degree of consistency between OP mappings, making words transparent. However, the omission of vowels in the script used by skilled readers makes the OP mappings of many words unpredictable or opaque. In this study, we used factor analysis to test which lexico-semantic variables, including AoA, predict the reading aloud of monosyllabic Persian words with different spelling transparencies (transparent or opaque). Linear mixed-effect regression analysis revealed that a Lexical factor (loading on word familiarity, spoken frequency, and written frequency) and a Semantic factor (loading on AoA, imageability, and familiarity) significantly predict word-naming latencies in Persian. Further analysis revealed a significant interaction between AoA and transparency, with larger effects of AoA for opaque than for transparent words and a significant interaction between imageability and AoA on reading opaque words; that is, AoA effects are more pronounced for low-imageability opaque words than for high-imageability opaque words. Interactions between these factors and spelling transparency suggest that late-acquired opaque words receive greater input from the semantic reading route. Implications for understanding the AoA effects on word naming in Persian are discussed.